Construction of the "Moment-Curvature" Scheme for Annular Cross-Sectional Reinforced Concrete Elements and its Application in the Calculatıon of Reinforced Concrete Beams - Hajiyev, M.A.; Damirov, M.M. (Herald of Azerbaijan Engineering Academy, 2024)
In solving the issues of rigidity of reinforced concrete elements, the determination of the displacements of these elements plays an important role. As you know, in order for these displacements to be determined, there must be a “moment-curvature" diagram. The authors have developed an effective numerical method for constructing a tabular dependence of the moment curvature diagram. In the article, an analytical expression was proposed that approximates diagrams in the form of a table with high accuracy, and the application of this dependence to the determination of deflections of reinforced concrete beams is shown. Based on the proposed methodology, displacements at an arbitrary load level can be determined using a single algorithm. It is shown that the influence of nonlinear deformation diagrams of materials on the value of deflections is strong, whereas the influence of static unsolvable diagrams on static unsolvability is weak. The effectiveness of the proposed calculation method was demonstrated by numerical examples.